Efficient callogenesis and Shoot organogenesis from nodal explants of Rosa hybrida L. (Lovely girl) - Seema, Nighat; Khan, Kiran Yasmin; Zakaria, Mohammad; Fazal, Hina (Journal of Research in Biology, 2012)
The callogenic and shoot organogenic potential of ornamental plant, Rosa hybrida were investigated. Callus induction and shoot regeneration were induced from nodal explants of garden plants incubated on Murashige and Skoog (MS)-medium supplemented with different concentrations of Plant Growth Regulators (PGRs). The best callus induction (80-85%) was observed on explants incubated on MS-medium supplemented with 2.0 mg l-1 6-benzyladenine (BA) and 1.5 mg l-1 BA along with 0.5 mg l-1 α-Naphthaleneacetic acid (NAA) or 0.5 mg l-1 2,4 dichlorophenoxyacetic acid (2,4 D) after four weeks of culture. When MS-medium supplemented with 1.5 mg l-1 BA alone induced 90% shoot organogenesis after 30-days following culture. 2.0 mg l-1 BA in combination with 1.0 mg l-1 Kin (Kinetin) also induced 90 % shooting. Moreover, when shoots were transferred to an elongation medium, the longest shoots (3.9 cm) were observed with similar composition of PGRs. The regenerated shoots were inoculated on rooting medium supplemented with different concentrations of Indole Butyric Acid (IBA), NAA and Indole Acetic acid (IAA) but no rooting was observed